Social Impact Management Assessment of Urban Flood is important-especially in Surabaya-Wonokromo and Surabaya-Brangkal - Soleh Soleh; Mohammad Sofyan (Yayasan Ilomata, 2020)
social assessment is a process that ensures that the execution of action reasonably informed and considered the critical social issues that are relevant, as well as providing a participation strategy for involving stakeholders at large. Socialization and Enforcement of laws and regulations related to particularly riverside following the normalization of physical development plan/development Wonokromo River flood control infrastructure and Brangkal should use a local culture aligned with the socio-economic, gender, and education of local people issues social surfaced in every area of study and assessment of the following community expectations and their advice on the results of the social assessment. In light of this, it expected that pre-construction, construction, and post-construction could be well supported by social security by the carrier the benefit of both the public, private, and government.